Performance indicators of piauienses in OBMEP: An application using coefficients and indexes based on population - Santos, Roberto dos; Sousa, Adriano Faustino de; Sousa, Raimundo Nonato; Silva, Eduardo de Moura dos Santos; Neto, Guilherme Luiz de Oliveira; Ferraz, Valmária Rocha da Silva; Macêdo, Gilmar Antônio Ribeiro de; Oliveira, Luiz Gustavo Farias de (Seven Editora, 2024)
This study aimed to seek a view of the performance of the state of Piauí in the OBMEP. More specifically, the proposal aimed to identify the municipalities whose performance is being influenced by the population variable and the municipalities where this does not happen, in addition to making comparisons of the performance of the state of Piauí with other Brazilian states, analyzing the population influence in the regional and national rankings, in order to obtain more consistent information to evaluate the temporal performance of Piauí in the OBMEP based on the data. The approach adopted is quantitative-qualitative, explanatory in nature, carried out with descriptive and exploratory objectives and with data collection procedures; Methods: statistical, hypothetical-deductive and comparative. As a result, it was possible to identify classifications for the performance of the State, according to association with population data, where it was classified in second position in the regional ranking of the competition, while in the national ranking its classification became in the tenth position. Finally, it was found that the population is among the variables that are related to performance in the OBMEP, in addition to public policies. Thus, it is concluded that this information highlights the good performance of Piauí in the OBMEP. DOI:https://doi.org/10.56238/sevened2024.007-065